CLIMATE CHANGE IN THE AMAZON AND THE NEW DISEASE PROFILE: CHALLENGES FOR GLOBAL HEALTH AND MULTIPROFESSIONAL PRACTICE - de Sales, Mariana Elizabeth Lopes; Rodrigues, Felipe Renato de Castro; de Sousa, Jacqueline Parente; Souto, Suane e Silva Duarte; Alves, Elda Lenilma Palheta; Pires, Patrícia Gabrielly da Silva; Melo, Jennifer Kelly Abreu; Santos, Kátia Lamara de Araújo; Gomes, Monize Lopes de Araújo; Mendonça, Gisele dos Santos; Correa, Amanda Emanuele dos Santos; de Oliveira, Dayvison Santos; et al. (Seven Editora, 2026)
Climate change has caused significant transformations in disease profiles, especially in environmentally sensitive regions such as the Amazon. This chapter aims to analyze how climate changes have been influencing epidemiological dynamics in the region, highlighting impacts on infectious diseases, chronic conditions, and environment-related health issues, as well as discussing the role of multiprofessional teams in this context. This is a qualitative study developed through an integrative review of the scientific literature, based on recent national and international publications. The findings show that factors such as deforestation, wildfires, and changes in climate patterns have contributed to the expansion of vector-borne diseases, the worsening of chronic conditions, and increased vulnerability among Indigenous and riverine populations. The emergence of new health risks associated with environmental degradation is also observed. In this scenario, the importance of the integrated work of physicians, nurses, pharmacists, physiotherapists, nutritionists, dentists, and public health professionals in surveillance, prevention, and comprehensive care is emphasized. It is concluded that understanding the new disease profile in the Amazon is essential to guide public policies and strengthen health systems better prepared for global health challenges.